2022
DOI: 10.3390/su141912795
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mediating Role of Place Attachment in the Link between Tourists’ Authentic Experiences of, Involvement in, and Loyalty to Rural Tourism

Abstract: The sustainable development of rural tourism is conducive to awakening “sleeping” resources, upgrading the industrial structure in rural areas, enhancing the revitalization ability of rural areas, accelerating the construction of cultural tourism, and promoting the strategy of rural revitalization. The loyalty of tourists has been considered as an important construct to describe the relationship between rural tourism growth and travelers’ future behavioral intentions. This study aims to integrate the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In a study by Hsu and Scott (2020) [ 18 ], it was suggested that food experience plays a crucial role in positively influencing place attachment in travel destinations. Similarly, Wang et al [ 80 ] conducted a study on rural tourism and found that tourism involvement significantly influences place attachment. Furthermore, Chen [ 81 ] investigated the relationship between involvement and place attachment in film tourism and discovered that celebrity involvement affects tourists’ place attachment to the destination.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Hsu and Scott (2020) [ 18 ], it was suggested that food experience plays a crucial role in positively influencing place attachment in travel destinations. Similarly, Wang et al [ 80 ] conducted a study on rural tourism and found that tourism involvement significantly influences place attachment. Furthermore, Chen [ 81 ] investigated the relationship between involvement and place attachment in film tourism and discovered that celebrity involvement affects tourists’ place attachment to the destination.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Tourism studies have revealed that both dimensions of place attachment (identity and dependence) positively impact tourists’ intention to recommend the destination to their friends or to revisit it [ 84 , 85 ]. Moreover, Wang et al [ 80 ] investigated the mediating role of place attachment in the context of rural tourism. The results of their study reveal that place identity and place dependence mediate the relationship between involvement and loyalty.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Through their wishes, tourists contribute directly to the formation of the tourist product, and through local and authentic experiences, the tourist destination becomes popular (Csurgó and Smith, 2021). Rural areas have their own authenticity, and the perception of this authenticity by tourists through the tourist experience helps to form the identity of the place, thus becoming a destination (Wang et al, 2022) Although rural tourism has been considered a factor contributing to local development (Iorio and Corsale, 2010), nowadays, this sector joins the other branches in tourism and holds a spot on the tourism market. Thus, the offer and the demand in the sector are factors that contribute to the existence and the development of this branch of tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have revealed that feeling nostalgic and deeply attached to a certain place or destination would profoundly influence people"s behavior regarding the place and motivate them to spread positive WOM. Additionally, it would result in loyalty which refers to the state of being emotionally and psychologically committed and willing to keep revisiting a certain destination (Wang et al, 2022;Lee and Jeong, 2021).…”
Section: Place Attachmentmentioning
confidence: 99%